Pengukuran, Perancangan, Keefektifan, Design Kurikulum MBKM PS DI UNJA - Iwan Putra; Novia Sri Dwijayanti; Ahmad Nasori; Nurmala Sari (Universitas Pahlawan, 2022)
Universities are required to be able to design and implement innovative learning processes so that students can achieve learning outcomes covering aspects of attitudes, knowledge, and skills. The form of the Independent Learning Campus (MBKM) policy can be used as a milestone for the answers to the problems faced so far. Methods This research was conducted through descriptive research with survey methods by submitting questionnaires to Lecturers and Students through Measurement, Design, Effectiveness, Respondents were selected randomly and proportionally (proportionate stratified random sampling. 5 MBKM activity programs have been implemented at Jambi University, namely in the form of Internship Activities/work practices with the number of participants participating in the activity 76 people, Teaching Assistance activities with 313 participants involved, Entrepreneurship activities with 127 participants, for students participating The MBKM program in the form of Thematic KKN activities is about 451 people, while 42 people are participating in the humanitarian program.